2011
DOI: 10.1088/0004-637x/742/2/110
|View full text |Cite
|
Sign up to set email alerts
|

Accretion of the Magellanic System Onto the Galaxy

Abstract: Our Galaxy is surrounded by a large family of dwarf galaxies of which the most massive are the Large and Small Magellanic Clouds (LMC and SMC). Recent evidence suggests that systems with the mass of the Local Group accrete galaxies in smaller groups rather than individually. If so, at least some of the Galaxy's dwarfs may have fallen in with the LMC and SMC, and were formed as part of the Magellanic system in the nearby universe. We use the latest measurements of the proper motions of the LMC and SMC and a mul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 43 publications
4
48
0
Order By: Relevance
“…Using a high-resolution dark-matter simulation of the local group, Libeskind et al (2011) concluded that the satellites of both MW and M31 were accreted anisotropically onto their haloes, entering the virial radius from a specific direction with respect to the large-scale structure. These conclusions are confirmed in other simulations of M31 dwarfs (Goerdt and Burkert 2013;Sadoun et al 2013), MW dwarfs (Nichols et al 2011;Lovell et al 2011), and in observations of dwarfs around NGC 3109 (Bellazzini et al 2013).…”
Section: Kinematical Distortionssupporting
confidence: 82%
“…Using a high-resolution dark-matter simulation of the local group, Libeskind et al (2011) concluded that the satellites of both MW and M31 were accreted anisotropically onto their haloes, entering the virial radius from a specific direction with respect to the large-scale structure. These conclusions are confirmed in other simulations of M31 dwarfs (Goerdt and Burkert 2013;Sadoun et al 2013), MW dwarfs (Nichols et al 2011;Lovell et al 2011), and in observations of dwarfs around NGC 3109 (Bellazzini et al 2013).…”
Section: Kinematical Distortionssupporting
confidence: 82%
“…The head-tail structure of high velocity clouds is another observation best explained in the context of a confining corona (Putman et al 2011). A separate argument for the existence of such a medium is the lack of detected HI in most dwarf spheroidal galaxies within 270 kpc of the Milky Way (Grcevich & Putman 2009) -a result that is naturally explained by ram pressure stripping by a ∼ 10 −4 cm −3 hot medium at ∼ 70 kpc (see also Moore & Davis 1994;Lin & Faber 1983;Nichols et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…For decades authors have speculated that some of the smaller Milky Way satellites may have originated with the Large and Small Magellanic Clouds (LMC, SMC; e.g., Lynden-Bell 1976;D'Onghia & Lake 2008;Nichols et al 2011;Sales et al 2011). The recent discovery of more than 20 ultra-faint ( M 8 V ) galaxy candidates by wide-area optical surveys, including the Dark Energy Survey (DES; Bechtol et al 2015;Drlica-Wagner et al 2015;Kim & Jerjen 2015;Koposov et al 2015a), the Survey of the MAgellanic Stellar History (SMASH ;Martin et al 2015), Pan-STARRS (Laevens et al 2015a(Laevens et al , 2015b, and VST ATLAS (Torrealba et al 2016a(Torrealba et al , 2016b, has renewed interest in identifying faint galactic companions of the Magellanic Clouds.…”
Section: Introductionmentioning
confidence: 99%